Synoptic-to-intraseasonal atmospheric modulation of phytoplankton biomass in the inner sea of Chiloé, Northwest Patagonia (42.5°-43.5°S, 72.5°-74°W), Chile - Jacques-Coper, Martín; Segura, Christian; de la Torre, María Belén; Valdebenito Muñoz, Pedro; Vásquez, Sebastián I.; Narváez, Diego A. (Frontiers in Marine Science, 2023)
The Inner Sea of Chiloé (ISC) in northwestern Patagonia has experienced large harmful algal blooms in the past decade, impacting human health and affecting the large aquaculture industry of the region. Thus, the investigation of factors favouring regional phytoplankton growth are of particular interest. Analysing the synoptic-to-intraseasonal variability, we explore changes in phytoplankton biomass in southern ISC (S-ISC, 42.5º-43.5ºS, 72.5º-74ºW) and their concurrent mesoscale and large-scale meteorological and oceanographic conditions. We use high-resolution satellite normalised fluorescence line height (nFLH) and chlorophyll-a (CHL-A) from the MODIS-Aqua sensor as proxies for phytoplankton biomass, besides oceanic and atmospheric variables derived from various remote-sensing sources and atmospheric fields from the ERA5 reanalysis. Specifically, we focus on high phytoplankton biomass events (HBE), which are defined as those cases when intraseasonal nFLH anomaly (nFLH’) exceeds the 95th percentile threshold. Each event was characterised by its first date of occurrence (called day 0). We detected 16 HBE between 2003 and 2019 in S-ISC. HBE occurred under the influence of a mid-latitude migratory anticyclone that induced persistent cloudless conditions preceding day 0, leading to enhanced photosynthetically active radiation (PAR) starting around day -8, and positive sea surface temperature (SST) anomalies between days -4 and 4. We hypothesise that HBE are mainly modulated by i) mixing and advection that could contribute to a greater availability of nutrients in the upper sea layers before the onset of the anticyclonic anomalies; and ii) increased thermal stratification related to positive PAR and SST anomalies that would promote phytoplankton growth during the anticyclonic regime. Furthermore, we show that the Madden-Julian Oscillation modulates the frequency of nFLH’ and thus of HBEs, a result that suggests an enhanced predictability of these cases.